Prognostic factors for mortality in patients with severe traumatic brain injury in Yogyakarta, Indonesia - Desin Pambudi Sejahtera; Ismail Setyopranoto; Indarwati Setyaningsih; Sri Sutarni; Tri Ratnaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Determining an accurate prognosis in patients with severe traumatic brain injury (TBI) still becomes a difficult challenge for neurologists. Clinical and laboratory findings have been used as important parameters to establish clinical decisions or even predict future prognosis including death in these patients. We studied the clinical, laboratory and neuroimaging parameters in predicting mortality in patients with severe TBI. This study used the medical records of severe TBI cases in Dr. Sardjito General Hospital, Yogyakarta, Indonesia from January 2015 until July 2016. We evaluated the clinical, laboratory, and neuroimaging examinations of seventy patients with severe TBI in association with mortality. The result showed among 70 patients involved, 35 were dead. Clinical findings of age <40 y.o. (OR=1.143; p=0.015), multiple injuries (OR=5.712; p=0.045), and systolic blood pressure >140 mmHg (OR=3.852; p=0.008) were associated with mortality. Laboratory and neuroimaging parameters of hyponatremia (OR=3.667; p=0.027), hyperkalemia (OR=1.771; p=0.030), and the presence of traumatic subarachnoid hemorrhage (SAH) (OR=6.526; p=0.003) in head CT-scan were significantly associated with mortality. In conclusion, our study showed that productive age <40 y.o. multiple injuries, hyponatremia, hyperkalemia and the presence of traumatic SAH increase the mortality risk in patients with severe TBI.